MANIFESTATIONS OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS-INDUCED KIDNEY DISORDERS - Tiwi Charisma (Faculty of Medicine Universitas Gadjah Mada, 2013)
INTRODUCTIONNon-steroidal anti-inflammatory drugs (NSAIDs) are one of the most commonly prescribed medication.1 The gastrointestinal tract and kidneys are important targets of clinical events associated with the use of NSAIDs.2 Selective COX-2 inhibitors have minimal gastrointestinal side effects. However, the newer NSAIDs also has nephrotoxic effects remain as nonselective NSAIDs.1The kidneys are the major organ for drug excretion, so that the renal arterioles and glomerular capillaries are especially vulnerable to the effects of drugs. 3 The spectrum of NSAID-induced nephrotoxicity includes acute tubular necrosis, acute tubulointerstitial nephritis, glomerulonephritis, renal papillary necrosis, chronic renal failure, salt and water retention, hypertension, and hyperkalemia. 1Among the various clinical complications, the effects on the kidney are probably the most common and severe due to the use of NSAIDs.4 Fifty million US citizens report NSAIDs use, and it has been estimated that 500.000 – 2,5 million people will develop NSAID nephrotoxicity in the US annually. 5 It has been reported that 37% of drug-associated acute renal failure is associated with the use of NSAIDs, and NSAID-induced acute renal failure accounts for 7% of overall cases of acute renal failure. 4This review discusses the NSAIDs, mechanisms and clinical manifestations of NSAID-induced renal impairment and some NSAID options that can be used in patients with renal failure.